2012
DOI: 10.1021/la302230z
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Computational Screening of Zeolites for Ethane/Ethene Separation

Abstract: Large-scale computational screening of thirty thousand zeolite structures was conducted to find optimal structures for separation of ethane/ethene mixtures. Efficient grand canonical Monte Carlo (GCMC) simulations were performed with graphics processing units (GPUs) to obtain pure component adsorption isotherms for both ethane and ethene. We have utilized the ideal adsorbed solution theory (IAST) to obtain the mixture isotherms, which were used to evaluate the performance of each zeolite structure based on its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 36 publications
3
86
0
Order By: Relevance
“…Accordingly, the atoms contributing to the creation of the binding site in these two materials are strikingly similar: 15 Si and 18 O, and 14 Si and 19 O, respectively (note these atoms are shared between multiple binding sites). In previous work, 46,47 we identified these 8-Si shapes for achieving favorable binding sites in zeolites for small hydrocarbon and CO 2 guest molecules; here we show that these features also yield optimal methane binding pockets in zeolites. Some materials do not have defined sites such as in model 0, but rather large, open surface areas of framework atoms that attract guest molecules.…”
Section: Analysis Of Top Performing Zeolite Structuressupporting
confidence: 68%
“…Accordingly, the atoms contributing to the creation of the binding site in these two materials are strikingly similar: 15 Si and 18 O, and 14 Si and 19 O, respectively (note these atoms are shared between multiple binding sites). In previous work, 46,47 we identified these 8-Si shapes for achieving favorable binding sites in zeolites for small hydrocarbon and CO 2 guest molecules; here we show that these features also yield optimal methane binding pockets in zeolites. Some materials do not have defined sites such as in model 0, but rather large, open surface areas of framework atoms that attract guest molecules.…”
Section: Analysis Of Top Performing Zeolite Structuressupporting
confidence: 68%
“…High-throughput screenings of porous materials can be found in the literature for vehicular natural gas storage, 22 carbon capture, 18,23 hydrogen storage, 24 ethene/ethane separations, 25 ethanol purification, 26 and sulfur dioxide removal.…”
Section: Introductionmentioning
confidence: 99%
“…(van Miltenburg et al, 2006) The low relative volatility of C 2 H 6 /C 2 H 4 mixture makes this process challenging. (Kim et al, 2012) Separation of C 2 H 6 from CH 4 is also important because natural gas is mainly composed of CH 4 and some heavy gaseous hydrocarbons such as C 2 H 6 . In order to obtain pure CH 4 , these two components must be separated.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoporous materials such as zeolites and carbon nanotubes have been previously studied for adsorption-based separation of C 2 H 6 /C 2 H 4 mixtures. (Gladden et al, 1997;Shi et al, 2010;Banerjee et al, 2015) Smit and coworkers (Kim et al, 2012) used molecular simulations to predict singlecomponent adsorption isotherms of C 2 H 6 and C 2 H 4 in zeolites. They then used Ideal Adsorbed Solution Theory (IAST) (Myers and Prausnitz, 1965) to estimate mixture adsorption isotherms from single-component adsorption isotherms and calculated C 2 H 6 /C 2 H 4 selectivity of zeolites at 1 bar and 300 K. Results showed that most zeolites exhibit C 2 H 6 selectivities in the range of 1-4 and working capacities less than 1.5 mol C 2 H 6 /kg material.…”
Section: Introductionmentioning
confidence: 99%